Improving Elementary Students’ Literacy and Numeracy through an Augmented Reality-Enhanced SmartBook - Armeria Wijaya; Linda Mayasari; Debio Pararta Wiguna; Gabriella Brahmasta Indra; Rizka Salsabila Sholihin (Room of Civil Society Development, 2025)
Previous studies on Augmented Reality (AR) in education have largely focused on vocabulary learning, reading comprehension, spatial reasoning, or mathematics skills using mobile or game-based platforms, mostly in international contexts. Research examining AR that is directly integrated into printed classroom materials remains limited, particularly studies aligned with Indonesia’s Kurikulum Merdeka and aimed at strengthening foundational literacy and numeracy. To address this gap, this study evaluated the effectiveness of SmartBook LKPD DigiLitNum, an AR-supported interactive workbook, in improving Grade 3 students’ literacy and numeracy performance. A one-group pre-test and post-test design was employed involving 35 students at UPT SDN 150 Gresik over 30 learning sessions. Standardized literacy and numeracy assessments were administered before and after the intervention. The results showed substantial improvements in both domains, with literacy scores increasing from a mean of 68.2 to 87.5 and numeracy scores from 66.2 to 86.9. Normalized gain scores ranging from 0.64 to 0.66 indicate moderate to high effectiveness. Classroom observations further revealed increased student engagement, participation, and learning motivation. These findings provide empirical evidence that AR-enhanced printed workbooks can function as practical and scalable learning resources for improving foundational literacy and numeracy in Indonesian elementary schools.